Determining numerical indicators for some biocritical abilities and their relationship to the accuracy of scoring among the players of the Fotsal specialized school in football - Hussein Qasim Hasan (Global Scientific Publishing, 2023)
The passage discusses the evolution of football as a sport and the efforts made to improve its performance and strategic development. It emphasizes that progress in football has come through research, study, critique, and analysis, particularly through courses and tournaments. The study also aimed to identify and measure certain biokinetic capabilities that affect goal accuracy. The research used a descriptive survey method, and the research sample was composed of 41 players from a specialized futsal school for football in Thi Qar province, out of a total of 72 players, representing 56.94% of the original research community. The research findings identified digital indicators for measuring biokinetic capabilities and designed a test for measuring goal accuracy while establishing a correlation between research variables. The recommendations include using these digital indicators to assess the biokinetic capabilities of football players and exploring other methods to generate digital indicators that align with the nature of assessing these capabilities and measuring goal accuracy in football. Furthermore, the study suggests conducting similar research on other fundamental
Keywords: fundamental; between; capabilities; measuring